PEMBELAJARAN ORGANISASI PADA PONDOK PESANTREN DALAM MEMASUKI ERA GLOBAL - Zainuddin, Moh. Riza (e-Journal STAI Muhammadiyah Tulungagung, 2013)
National problems that never ended, ranging from the economic slump, a leadership crisis, a moral crisis, the environmental crisis to the threat of terrorism, requires all the elements and components of the nation to stand and take part as a problem solver. No exception with a wide range of potential schools that are still hidden treasures tub. This is one of the major challenges of our times, how big the potential raises pesantren became a real contribution to society and the nation.